2017
DOI: 10.3390/ma10070827
|View full text |Cite
|
Sign up to set email alerts
|

Simulations on Monitoring and Evaluation of Plasticity-Driven Material Damage Based on Second Harmonic of S0 Mode Lamb Waves in Metallic Plates

Abstract: In this study, a numerical approach—the discontinuous Meshless Local Petrov-Galerkin-Eshelby Method (MLPGEM)—was adopted to simulate and measure material plasticity in an Al 7075-T651 plate. The plate was modeled in two dimensions by assemblies of small particles that interact with each other through bonding stiffness. The material plasticity of the model loaded to produce different levels of strain is evaluated with the Lamb waves of S0 mode. A tone burst at the center frequency of 200 kHz was used as excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…According to previous studies [ 7 , 8 , 9 , 10 , 12 , 13 , 14 , 18 , 19 , 20 , 23 , 24 ], the measured acoustic nonlinearity parameter of Lamb waves can be expressed as , where, and are the measured amplitudes of the fundamental and the second harmonic signals, respectively. Here, the expressions and are adopted to measure the acoustic nonlinearity, where, is the measured amplitude of the zero-frequency mode.…”
Section: Acoustic Nonlinearity Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous studies [ 7 , 8 , 9 , 10 , 12 , 13 , 14 , 18 , 19 , 20 , 23 , 24 ], the measured acoustic nonlinearity parameter of Lamb waves can be expressed as , where, and are the measured amplitudes of the fundamental and the second harmonic signals, respectively. Here, the expressions and are adopted to measure the acoustic nonlinearity, where, is the measured amplitude of the zero-frequency mode.…”
Section: Acoustic Nonlinearity Parametermentioning
confidence: 99%
“…Previous works have shown that the techniques based on nonlinear Lamb waves can be utilized for long-range and in-depth inspection [ 7 , 8 , 9 ] through characterizing acoustic nonlinearity, which in turn can be regarded as an indicator of the early-stage material nonlinearity caused by fatigue plasticity, precipitation hardening of thermal aging, corrosion, etc. [ 10 , 11 , 12 , 13 , 14 ]. In general, a nonlinear response is generated in the region where the early-stage material nonlinearity occurs and then several nonlinear wave components may appear including subharmonics or higher-order harmonics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear ultrasound has been found to be a useful indicator of the material damage within large plate-like structures for nondestructive evaluation and structural health monitoring, since they are sensitive to microstructural evolution at the early stage of material degradation when compared with the conventional linear ultrasounds [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The long propagation distance and the interrogation of the entire thickness of plate-like structures make nonlinear Lamb wave a highly efficient inspection method.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ]. Recently, many studies focused on the second harmonic generation (SHG) to characterize the material nonlinearity [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Due to the dispersive and multimode natures, the propagation of Lamb waves is complex and the double frequency Lamb waves (DFLWs) are generally weak.…”
Section: Introductionmentioning
confidence: 99%